Pencegahan Pelanggaran Tindak Pidana Pemilu melalui Pendaftaran dan Verifikasi Partai Politik Berdasarkan Undang-Undang Pemilu - Fauzi, Muhammad Oky; Prasetyoningsih, Nanik (Universitas Muhammadiyah Yogyakarta, 2024)
After 24 years of reform, the people passionately anticipate direct general elections as a process of power transition and evaluation of the performance of political parties over the previous five years. Similarly, the registration and verification phases of political parties participating in the 2024 Election, which began on Friday, July 29, 2022, and ended on Tuesday, December 13, 2022, have concluded for the 2024 Election. The requirement for verification of political parties is an effort to improve the institutions of political parties to make them more professional in their management, as well as to verify the readiness and fulfillment of the requirements of political parties, both new and those that have participated in previous elections. In addition, if the registration and verification of political parties process proceeds smoothly, the subsequent stages will also go smoothly. One is to minimize or prevent violations of election criminal acts that can diminish the wisdom and efficiency of the 2024 Election process and stages. This study uses normative and empirical research methods and qualitative analysis to examine the relationship between the registration and verification of political parties and efforts to prevent election crime violations. This study demonstrates that verifying political party candidates can assist electors in selecting credible and competent public officials. However, verification provisions and procedures can increase the chance of election crimes and electoral misconduct. Therefore, the election commission (KPU) and Bawaslu must be resolute and unaffected by any interference that could harm the integrity of elections and democracy. The community is also responsible for supervising and providing aspirations so that election regulations do not diminish enthusiasm for conducting elections with integrity.